Cosmopolitanism of Langsa Society during Colonial Era - Sumiyati, Sumiyati; Sulistiyono, Singgih Tri; Rochwulaningsih, Yety; Azhari, Ichwan (Diponegoro University, 2024)
The advent of modernization in the 19th century significantly influenced the development of Langsa City, Aceh Province, as a cosmopolitan city. Despite having a strong Islamic tradition, Langsa was able to embrace cosmopolitanism without losing its Acehnese identity. This study focuses on the influence of cosmopolitanism on the socio-cultural life of the Langsa community. Cosmopolitanism in Langsa also influenced the lifestyle of its people, as seen in their global thinking and the perspectives of the educated elite. The research findings indicate that cosmopolitanism in Langsa has been ongoing for a long time, starting from the pre-Islamic era, continuing through the waves of European and other foreign arrivals, the influence of colonialism, independence, the arrival of modernist Islam, and up to the New Order political era. With abundant natural resources, Langsa has attracted foreigners. The interaction of people from various nations has led to the convergence of diverse cultures. However, despite being influenced by external cultures, the people of Langsa have also maintained their original culture amidst a hybrid culture. This is partly because the native people of Langsa, in their lifestyle, tend to follow the ulama(religious scholars) rather than the umara (secular leaders). As a cosmopolitan city, Langsa has also become a meeting place for modernist thoughts. One example is the acceptance of Muhammadiyah as a modernist Islamic organization.